Comparative Effects of Sulforaphane and Allyl Isothiocyanate on 3T3-L1 Adipogenesis - Satoru Sakuma; Kana Yasuda; Risa Kitahara; Kaho Tsujimoto; Kishiko Yamashita; Naohiro Hoshino; Yohko Fujimoto; Keiichiro Okuhira (Journal of Nutrition and Metabolism)
Sulforaphane and allyl isothiocyanate, naturally occurring isothiocyanates, have been reported to inhibit adipocyte differentiation, but little is known about how they compare in terms of their potency and mechanism of action. In the present study, we compared the effects of sulforaphane and allyl isothiocyanate on the differentiation of 3T3-L1 preadipocytes. A mixture of insulin, dexamethasone, and 3-isobutyl-1-methylxanthine was used to establish a differentiation medium. We found that, at a concentration as low as one-tenth that of allyl isothiocyanate, sulforaphane reduced triacylglycerol levels, lipid-filled adipocyte quantity, and mRNA and protein levels of CCAAT-enhancer-binding protein α (C/EBPα) and peroxisome proliferator-activated receptor γ (PPARγ). These results suggested that sulforaphane may be a more potent adipocyte differentiation inhibitor than allyl isothiocyanate. Our results may provide insight into possible strategies for the prevention of obesity and related conditions.